Trainee and Program Director Perceptions of Quality Improvement and Patient Safety Education: Preparing for the Next Accreditation System. (November 2014) - Zenlea, Ian S.; Billett, Amy; Hazen, Melissa; Herrick, Daniel B.; Nakamura, Mari M.; Jenkins, Kathy J.; Woolf, Alan D.; Kesselheim, Jennifer C.
Objective . To assess the current state of quality improvement and patient safety (QIPS) education at a large teaching hospital. Methods . We surveyed 429 trainees (138 residents, 291 clinical fellows) and 38 program directors (PDs; 2 were PDs of >1 program) from 39 Accreditation Council for Graduate Medical Education–accredited training programs. Results . Twenty-nine PDs (76.3%) and 259 trainees (60.3%) responded. Most trainees (68.8%) reported participation in projects culminating in scholarly products (39.9%) or clinical innovations (44%). Most PDs reported that teaching (88.9%) and project supervision (83.3%) are performed by expert faculty. Nearly half of the PDs (45.8%) and trainees (49.6%) perceived project-based learning to be of equal value to formal curricula. Compared with trainees, a greater proportion of PDs reported needs for funding for projects, teaching faculty to provide mentorship, and faculty development ( P < .05). Conclusions . Providing additional financial, administrative, and operational support could enhance the value of curricula and projects. Developing expert teaching faculty is paramount.